Mental health conceptualization and resilience factors in the Kalasha youth: An indigenous ethnic and religious minority community in Pakistan - Riaz, Fahad; Khan, Tahir M.; Park, Miriam Sang-Ah; Golden, Karen J. (2018)
The Kalasha are a religious, ethnic, and linguistic minority community in Pakistan. They are indigenous people living in remote valleys of the Hindu Kush Mountains in northern Pakistan, neighboring Afghanistan. The Kalasha are pastoral, as well as agricultural people to some extent, although they are increasingly facing pressures from globalization and social change, which may be influencing youth and community development. Their traditional world view dichotomizes and emphasizes on the division of the pure (Onjeshta) and the impure (Pragata). There remains a scarcity of literature on mental health and resilience of indigenous communities in South Asia and Pakistan generally, and the polytheistic Kalasha community specifically. Thus, the current study was conducted with the aim to explore the cultural protective factors (resilience) of the Kalasha youth (adolescents and emerging adults) and to explore their perceived etiological understandings and preferred interventions for mental health support systems. The theoretical framework of Bronfenbrenner's (1, 2) ecological systems model was used. Interpretative Phenomenological Analysis (IPA) was conducted, considering the advantage of its idiographic approach and the “double hermeneutic” analytic process. This methodology was consistent with the aim to understand and make sense of mental health and resilience from the Kalasha indigenous perspective. A total of 12 in-depth interviews were conducted with adolescents and emerging adults (5 males, 7 females), along with ethnographic observations. The analysis revealed 3 superordinate themes of mental health perceptions and interventions, each with more specific emergent themes: (1) Psychological Resilience/Cultural Protective Factors Buffering Against Mental Health Problems (Intra-Communal Bonding & Sharing; Kalasha Festivals & Traditions; Purity Concept; Behavioral Practice of Happiness and Cognitive Patterns); (2) Perceived Causes of Mental Health Issues (Biological & Psychosocial; Supernatural & Spiritual; Environmental); and (3) Preferred Interventions [Shamanic Treatment; Ta'awiz (Amulets); Communal Sharing & Problem Solving; Medical Treatment; Herbal Methods]. The overall findings point to the need for developing culturally-sensitive and indigenous measures and therapeutic interventions. The findings highlighted the Kalasha cultural practices which may promote resilience. The findings also call for indigenous sources of knowledge to be considered when collaboratively designing public health programs